Clathrin Light Chains: Not to Be Taken so Lightly - Das, Jyoti; Tiwari, Mahak; Subramanyam, Deepa (Frontiers in Cell and Developmental Biology, 2021)
Clathrin is a cytosolic protein involved in the intracellular trafficking of a wide range of cargo. It is composed of three heavy chains and three light chains that together form a triskelion, the subunit that polymerizes to form a clathrin coated vesicle. In addition to its role in membrane trafficking, clathrin is also involved in various cellular and biological processes such as chromosomal segregation during mitosis and organelle biogenesis. Although the role of the heavy chains in regulating important physiological processes has been well documented, we still lack a complete understanding of how clathrin light chains regulate membrane traffic and cell signaling. This review highlights the importance and contributions of clathrin light chains in regulating clathrin assembly, vesicle formation, endocytosis of selective receptors and physiological and developmental processes.